A study on the ‘gotong-royong’ spirit among society in Melaka Tengah (a case study on Taman Kerjasama and Kampung Bachang) - Mohamad Kassim, Siti Nor Faizah; Mohd Ahyan, Nurabidah (2008)
Ensuring the spirit of gotong-royong among public by our government is important due to the era of globalization. This is because the aim and goal of this spirit of gotong-royong is to maintain and retain the peace and harmonies of the nation. In Malaysia we have various races like Malay, Chinese and Indian that has their own belief that most of this religious are encouraging all the society live in the spirit of tolerance and gotong-royong attitude. Therefore this research is focuses the measuring on factor that encourage spirit of gotong-royong whether it come from environment, social status, education, demographic, types of gotong-royong and togetherness. This research was carry carried out at Melaka Tengah area which 150 questionnaires using multistage cluster sampling distributed to society at Kampung Bachang and Taman Kerjasama. We choose two different locations because we want to know how far the spirit of gotong- royong between Kampung and Taman and also the difference perception on dealing with spirit of gotong-royong. From our finding gotong-royong spirit still exist in both location which is they agree that gotong-royong will give benefit for themselves. In addition, most society also agreed that gotong-royong participation not need to pay on their contribution but it can be use if society is given recognition for their involvement. In conjunction on that society also strongly support to the implementation of “Hari Gotong- Royong se-Malaysia” to bring the integration of unity.